Formulation of high potassium and fiber snack bar based on seaweed, kepok banana, and mocaf flour as an alternative snack for hypertension patients - Indah Kusumaningrum; Nur Setiawati Rahayu (UHAMKA PRESS, 2018)
Hypertension is a case that affects many elderly people, this disease can interfere with the functioning of other organs, especially vital organs such as the heart and kidneys. According to prevalence data, hypertension patients in Indonesia were 26.5 percent. Patients exposed to this case at the age of ≥18 years were 25.8% and patients who have normal blood pressure and take hypertension medication were 0.7% (Riskesdas, 2013). Hypertension sufferers are advised to reduce sodium and saturated fat intake and increase potassium intake. Seaweed and kepok banana are foods that have high potassium content. Seaweed and mocaf also have high fiber content. So that these materials can potentially be developed into raw materials for making alternative food products for people with hypertension. The research was conducted in two stages, the first phase of the research was seaweed extraction and the manufacture of kepok banana flour. The second phase of the study was a formulation of fortified snack bar with composite flour (seaweed flour, kepok banana flour, and mocaf) obtained in the first stage. Then sensory analysis included hedonic test. The most preferred formula for panelists was formula 3, both in aroma, taste, and texture with a mixture of 75% composite flour and nutritional content in 100 grams containing calories around 307.70 kcal. The content of fiber per 100 gram of snack bar was about 8.44 gram and potassium was and 430.11 mg. Keywords: Snack Bar, Hypertension, Composite Flour, High Dietary Fiber, High Potassium